Effect of depression and empowerment on medication adherence in patients with breast cancer: a descriptive survey - Sookyung Jeong; Eun Jeong Kim (BMC Nursing)
Abstract Background Given the global prevalence of breast cancer and its high mortality rate, adherence to long-term anti-hormonal therapy is crucial for preventing recurrence and improving survival outcomes. Previous research demonstrates how psychological factors including depression and empowerment impact medication adherence. However, comprehensive studies remain limited, especially in Korea. This study explores the effects of depression and empowerment on medication adherence among patients with breast cancer undergoing anti-hormonal therapy. Methods This descriptive survey involved 183 patients with breast cancer from one hospital in South Korea; participants were recruited using convenience sampling. Self-reported questionnaires were used to assess medication adherence, depression levels using the Korean version of the Beck Depression Inventory-II, and empowerment levels using a tool developed for women with breast cancer. Hierarchical regression explored relationships and influences between variables. Results Participants demonstrated an average depression score of 19.67 ± 11.25, with medication adherence measured at 18.06 ± 5.15 and empowerment at 106.40 ± 18.15, revealing that, among patients with breast cancer, many experienced depression with varying levels: 16.9% mild, 27.3% moderate, and 21.9% severe. Medication adherence levels were distributed, with 58.5% of patients categorized as non-adherent and 41.5% categorized as adherent. The results indicated a significant negative correlation between depression and medication adherence and a positive correlation between empowerment and medication adherence. Higher empowerment levels were associated with improved adherence. Conversely, high depression levels were associated with low medication adherence. Conclusions This study enhances understandings of psychosocial factors influencing medication adherence in patients with breast cancer, highlighting patient empowerment as crucial for healthcare interventions. Thus, healthcare providers should implement targeted interventions including educational programs to inform patients about their treatment regimens, provide counseling services addressing mental health concerns such as depression, and establish support groups fostering a sense of community and shared experiences among patients. By integrating these strategies into patient care, healthcare professionals can significantly enhance patient empowerment and improve medication adherence toward better health outcomes for breast cancer patients. Future research could explore the long-term effects of these interventions on adherence and overall patient well-being.